Automatisierte Wissenskommunikation - Holste, Alexander (Wissenskommunikation / Knowledge Communication AMP, 2024)
The use of self-adaptive, AI/LLM-based machines is currently disruptively changing the subject area of multilingual specialist communication research. The discipline runs the risk of no longer being able to grasp the new developments through its current models and instruments and thereby marginalizing itself. Alexander Holste's model of automated knowledge communication responds to this challenge: It represents the cognitive-emotive construction of specialist knowledge by a situated knowledge actor in exchange with a language-processing machine. The model of this habilitation thesis is based on an impressive overview of the research discourse and integrates approaches from cybernetics, sociology of technology and media psychology. In a forward-looking way, it offers a program for the further development of specialist communication research towards knowledge orientation and the role of increasingly automated machines - automated knowledge communication.